2019
DOI: 10.1002/lary.28317
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Dysphagia and Airway Protection in Infants with 22q11.2‐Deletion Syndrome

Abstract: Objective: 22q11.2-deletion syndrome is a genetic condition that affects 1:3000 births. In addition to cardiac anomalies and immunosuppression, individuals with 22q11.2-deletion syndrome can have feeding difficulties from birth resulting in failure to thrive and infections. This study aims to characterize the dysphagia seen in infants with 22q11.2-deletion syndrome. Methods: This is a retrospective chart review of infants with 22q11.2-deletion syndrome who underwent videofluoroscopic swallow studies (VFSS) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
2
13
0
1
Order By: Relevance
“…Some behavioral sex differences have been described in individuals with 22q11DS: males tend to be more withdrawn, have more somatic complaints, and are more likely to have anxiety and depression than females (22). Nevertheless, the incidence of dysphagia and other airway abnormalities in 22q11DS does not differ between males and females (1,10,(23)(24)(25)(26). In addition, our previous research with adult C57BL/6J mice revealed no significant differences in swallowing function between sexes (13).…”
Section: Fluoroscopic Assessment Of Feeding and Swallowingmentioning
confidence: 86%
“…Some behavioral sex differences have been described in individuals with 22q11DS: males tend to be more withdrawn, have more somatic complaints, and are more likely to have anxiety and depression than females (22). Nevertheless, the incidence of dysphagia and other airway abnormalities in 22q11DS does not differ between males and females (1,10,(23)(24)(25)(26). In addition, our previous research with adult C57BL/6J mice revealed no significant differences in swallowing function between sexes (13).…”
Section: Fluoroscopic Assessment Of Feeding and Swallowingmentioning
confidence: 86%
“…Features of 22q11DS vary widely even in individuals with the same deletion (McDonald‐McGinn et al, 2015). While cardiac and craniofacial dysmorphology as well as a broad range of behavioral disabilities are among the most well‐known features of 22q11DS, almost all 22q11DS patients exhibit some degree of feeding and swallowing problems during childhood, a disorder known as pediatric dysphagia (Dyce et al, 2002; Eicher et al, 2000; Grasso et al, 2018; Jones, Tracy, Perryman, & Arganbright, 2018; Maggadottir & Sullivan, 2013; McDonald‐McGinn et al, 2015; Wong et al, 2019). Infants with 22q11DS gag, regurgitate and aspirate during feedings and have difficulties advancing the volume of feeds (Dyce et al, 2002; Eicher et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Infants with 22q11DS gag, regurgitate and aspirate during feedings and have difficulties advancing the volume of feeds (Dyce et al, 2002; Eicher et al, 2000). Aspiration during swallowing is a major factor contributing to frequent respiratory, sinus and ear infections observed in 22q11DS patients (Eicher et al, 2000; Grasso et al, 2018; Jones et al, 2018; Maggadottir & Sullivan, 2013; Wong et al, 2019). Approximately half of children with 22q11DS exhibit difficulties with feeding after the first year of age and a third struggle with advancing to textured foods (Eicher et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These data confirmed that mesenchymal Tbx1 is necessary for pharyngeal arch development (Zhang, Huynh and Baldini, 2006) and mutation in Tbx1 gene is closely associated with the etiology of DiGeorge syndrome. In patients, DiGeorge syndrome, or velo-cardio-facial syndrome, is linked with the 22q11.2 microdeletion (Wong et al, 2019), which alters Tbx1 gene expression (Lipson et al, 1991;Chieffo et al, 1997;Morrow et al, 2018). Besides congenital heart defects and craniofacial malformations, these patients exhibit a wide range of laryngeal abnormalities including laryngeal webs (the most frequent anomaly), subglottic stenosis, laryngomalacia and/or atrophic VF (Fokstuen S, Bottani A, Medeiros PF, Antonarakis SE, Stoll C, 1997; Ebert et al, 2018).…”
Section: Signaling Pathways That Control Migratory Cell Populations and Differentiation Of The Mesenchymal Progenitorsmentioning
confidence: 99%